2008
DOI: 10.1159/000129664
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and Climatic Associations with Violent and Nonviolent Suicide: A Population-Based Study

Abstract: Background: Using 7-year population-based data on Taiwan, we examined seasonal variation in violent versus nonviolent suicide, and its association with meteorological factors: ambient temperature, relative humidity, atmospheric pressure, rainfall and daily sunshine hours. Methods: We used Taiwan’s nationwide mortality data from 1997 to 2003, categorizing the sample decedents into two groups, violent (ICD-9-CM codes E953–E958) and nonviolent (E950–E952) suicide, based on the suicide method used. Seasonal autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
7
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 54 publications
7
59
7
4
Order By: Relevance
“…In agreement with the prior study of us ) and Oravecz et al (2006) these fi ndings also indicate that decreasing seasonality of suicides could be a good marker of lowering rate of depression-related suicides in the population, particularly in males who use much more frequently violent suicide methods (Maes et al 1993;Kim et al 2004;Lin et al 2008). As gender distribution, method preference, psychiatric morbidity and seasonality of suicides in Hungary (Murphy 2000;Voracek et al 2004;Berecz et al 2005;Kalmar et al 2008) is the same as in other European and North American countries (Murphy 2000;Maes et al 1993;Voracek et al 2004;Oravecz et al accompanied by a sharp increase of suicide mortality in that age-groups while suicide rates further de creased in older people where the utilization of ADs further increased or declined only slightly.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with the prior study of us ) and Oravecz et al (2006) these fi ndings also indicate that decreasing seasonality of suicides could be a good marker of lowering rate of depression-related suicides in the population, particularly in males who use much more frequently violent suicide methods (Maes et al 1993;Kim et al 2004;Lin et al 2008). As gender distribution, method preference, psychiatric morbidity and seasonality of suicides in Hungary (Murphy 2000;Voracek et al 2004;Berecz et al 2005;Kalmar et al 2008) is the same as in other European and North American countries (Murphy 2000;Maes et al 1993;Voracek et al 2004;Oravecz et al accompanied by a sharp increase of suicide mortality in that age-groups while suicide rates further de creased in older people where the utilization of ADs further increased or declined only slightly.…”
Section: Resultssupporting
confidence: 90%
“…Whether our fi ndings on the gender differences in antidepressant userelated seasonality change of suicide mortality are independent of the type of suicide methods (violent vs. non-violent) or restricted only to violent suicides, which have been shown to have more marked seasonality (Maes et al 1993;Lin et al 2008) remains an open question and is the subject of further studies.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been demonstrated that methodological choices can substantially influence the findings of changes after a disaster event (Norris, 2006), and an important limitation of extant studies of the September 11, 2001 disaster is that they have generally failed to account for variation in long-and short-term trends in suicide rates in their analytic approach (Dominici, Levy, & Louis, 2005;Lin, 2008). Traditional pre-and postdisaster comparisons may not control for time-varying factors that may be coincident with the study timeframe or explicitly test the causal nature of the exposureoutcome relationship (Kerlinger & Lee, 2000).…”
mentioning
confidence: 99%
“…Sarina test je statistički značajan za oba pola (p<0,001) za nasilne, ali ne i za nenasilne suicide. Isto tako, dokazan je porast suicida s porastom sobne temperature [12].…”
Section: Klimatske Varijacije Kod Nasilnih I Nenasilnih Suicidaunclassified